PENGARUH AKTIVITAS WISATA BUDAYA TERHADAP PELESTARIAN BUDAYA TIONGHOA: BUKTI DARI PURA BOEN TEK BIO - Jasica Kristin Mangkey; Muhamad Zhabiyan Dwi Putra (Institut Agama Hindu Negeri Gde Puda Mataram, 2026)
This study aims to analyze the impact of cultural tourism activities on the preservation of Chinese culture at the Boen Tek Bio Temple in Tangerang. This study is motivated by the growing role of cultural tourism as a means of preserving ethnic identity amid modernization and globalization. The research method employed is a quantitative approach with a descriptive design. Data were collected through a questionnaire administered to 100 respondents, comprising tourists and local residents, using purposive sampling. Data analysis was conducted through validity and reliability tests, descriptive analysis, and simple linear regression. The results indicate that cultural tourism activities have a positive and significant influence on the preservation of Benteng Chinese culture. This suggests that the higher the level of engagement in cultural activities such as festivals and religious rituals, the higher the level of awareness, knowledge, and participation in cultural preservation. These findings reinforce the role of cultural tourism not only as an economic activity but also as a medium for strengthening social identity and cultural sustainability. This study contributes to the development of cultural tourism studies, particularly in the context of preserving the culture of ethnic minorities, and underscores the importance of sustainable tourism management grounded in cultural values.